2006
DOI: 10.2500/ajr.2006.20.2947
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Epithelial Adenomatoid Hamartomas and Chondroosseous Respiratory Epithelial Hamartomas of the Sinonasal Tract: A Case Series and Literature Review

Abstract: Misdiagnosing REAH or CORE hamartoma as either inverted papilloma or adenocarcinoma may lead to far more aggressive surgical intervention then is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…Although conservative surgical excision of REAH in humans is considered curative, 1 distinguishing hamartomas from inverted papilloma or adenocarcinoma is important to prevent more aggressive surgical approaches. 10 Histologically, the mass in the dog in the current study had criteria for the diagnosis of REAH. The inflammatory infiltrates were considered secondary and were most likely a result of decreased bacterial clearance due to the extensive turbinate loss.…”
mentioning
confidence: 81%
“…Although conservative surgical excision of REAH in humans is considered curative, 1 distinguishing hamartomas from inverted papilloma or adenocarcinoma is important to prevent more aggressive surgical approaches. 10 Histologically, the mass in the dog in the current study had criteria for the diagnosis of REAH. The inflammatory infiltrates were considered secondary and were most likely a result of decreased bacterial clearance due to the extensive turbinate loss.…”
mentioning
confidence: 81%
“…It was first described by Wenig and Heffner as a benign overgrowth of submucosal ciliated respiratory lined glands forming a polypoid mass lesion [11]. The majority arise from the posterior nasal septum, more commonly in males between the ages of 27 and 81, who present with obstructive symptoms or epistaxis [9][10][11]. It was suggested that they may be associated with other lesions, such as inverted papilloma and solitary fibrous tumor, but no definite precursor lesions have been identified [3].…”
Section: Discussionmentioning
confidence: 99%
“…In the sinonasal region, hamartomas have been designated as epithelial, mesenchymal, and mixed [3,4]. They include chrondomesenchymal hamartoma [4][5][6][7], respiratory epithelial adenomatoid hamartoma (REAH) [8][9][10][11], and seromucinous hamartoma (SH). Each of these has characteristic features, but occasional lesions will show overlapping features of multiple types.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of so-called COREAH (chondroosseous REAH) have been described, where either cartilage or bone are present within a REAH [7,8], which still could be in keeping with a hamartomatous process given the normal appearance of these structures in the nasal cavity. The chondro-osseous components could alternatively be normal structures entrapped by the REAH rather than a part of the proliferation.…”
Section: Respiratory Epithelial Adenomatoid Hamartomamentioning
confidence: 99%